Uncovering Unexpected Actors in an Educational Service Ecosystem - Rothe, Hannes; Gersch, Martin (1. Jahrestagung der Wissenschaftlichen Kommission Dienstleistungsmanagement (WK DLM), 2016)
A crucial factor of improving IT-based services lies within the boundaries of understanding its usage. This is especially true for highly integrated services, like educational service (Shostack 1982), as value co-creation is based upon usage processes (Prahalad and Ramaswamy 2004; Vargo and Lusch 2004). Usage can be assumed as a process of (autonomous) resource integration between several actors. Therefore, Lusch and Vargo (2014) draw on relatively self-contained, and self-adjusting systems” (p. 161), they call service ecosystems. Self-containment and self-adjustment are a result of inherent self-supporting and loosely-coupled actors, who mainly share two things: (1) a will to co-create value, and (2) institutional logics, like rules and standards, which mediate their actors coupling. As each actor in a service ecosystem chooses on its own, which resources it integrates into value-co-creation, the number and type of actors become may become less pre-determined and less expectable for focal service suppliers. We choose to take a traditional supplier-perspective and ask: How do resource-integrating users autonomously – and therefore unexpectedly – integrate actors into value co-creation processes?